Oil prices fluctuations and stock market performance: does uncertainty matter? / Noor Zahirah Mohd Sidek - Mohd Sidek, Noor Zahirah (2019)
Bloomberg reported that Malaysia is one of the most 'boring' stock market where it is the only market losing out in Asia and stock market remained 'bearish' since "... there is nothing to be positive about over the next 12 months" (Bloomberg, 15 April 2019). In the first quarter of 2019, the Malaysian stock market saw an exodus of more than USD500 million. It is alleged that changes in the ruling party in the 14th General Election followed by unclear policy directions being one of the contributing factors. The first week after the 14th General Elections witnessed the normal downturn of 75 points to 1,841 points, as foreign investors start to sell the shares and continued to plunge down to 1,660 points when investors start to make 'technical corrections', account for the risks following announcements of cancellation of projects under previous government and other policy uncertainties. The fluctuations did not dissipate and up to March 2019, KLCI continue to trade at 1,679.9 point despites predictions that the market should hit 1,900 point. The reasons cited were external shocks perpetuating to Malaysia such as China's export slump, lower Euro Zone economic growth and inflation forecast and overall fall in the world's major stock markets. Despite the upward movement of crude oil prices in the first quarter of 2019, the stock market remained gloomy. Changes in oil price directly affect other macroeconomic variables. An increase in oil price may lead to increases in the production costs stemming from increments in transport and raw material costs. Consequently, inflation, interest rates and terms of trade will follow suit which later affects investments and economic growth. Meanwhile, the government revenue is expected to fall due to changes of taxation system from GST to SST. The overestimated oil prices revenue in the last year's budget of around USD70 per barrel poses a possibility of higher deficit, all of which leads to uncertainty in the market.